Approach to suspected donor-derived infections - Bahakel, Hannah Kinard; Pellet Madan, Rebecca; Danziger-Isakov, Lara (Frontiers in Pediatrics, 2023)
Prevention of donor-derived disease among pediatric solid organ transplant recipients requires judicious risk-benefit assessment. Comprehensive guidelines outline specific donor risk factors and post-transplant monitoring strategies to prevent and mitigate transmission of HIV, hepatitis B, and hepatitis C. However, elimination of unanticipated donor-derived infections remains challenging. The objectives of this review are to 1) define risk of anticipated versus unanticipated disease transmission events in pediatric solid organ transplant recipients; 2) discuss donor presentations that confer greater risk of unanticipated disease transmission; 3) develop a matrix for consideration of donor acceptance; and 4) discuss limitations and future directions for donor screening. Although solid organ transplant confers inherent risk of infection transmission, the risk of significant disease transmission events may be mitigated by a comprehensive approach including donor assessment, consideration of recipient need, post-transplant monitoring, and early intervention.